Development Strategy for Salt Farmers Market Access in East Java Indonesia: SWOT Analysis Approach - Mustofa,; Komariyah, Siti; Yuliati, Lilis; Supeni, Nely (International Journal of Social and Administrative Sciences, 2021)
Salt production in Indonesia, known as a maritime country, has not been able to meet national needs. On the other hand, salt is a very basic product which almost all industry activities require raw salt, besides salt is also a basic necessity for people's lives. This problem was resolved by importing salt from abroad, but this then harmed salt production activities in Indonesia, especially in East Java. The purpose of this research is to form a market share development strategy owned by salt farmers in eastern Java. The method used in this study is an in-depth interview and the SWOT analysis method that can form the most efficient strategy for the problems encountered. Based on the results of field observations, it shows that the problem that occurs in the institutional system pattern of salt in the downstream area is that there is a non-formal loan system between salt farmers and middlemen who do not have written regulations and weaken salt farmers in determining the price of salt. Then, based on the results of the SWOT analysis, it shows that to expand market access for salt farmers, an institutional design is required in which there is government intervention.